Exploring the Uses and gratifications of Youtube, Instagram, and Tiktok among Undergraduate Students of Abubakar Tafawa Balewa University, Bauchi - Kayode Sunday John Dada; Yunana Gladys MUSA (Journal in Teaching and Education Area, 2026)
This quantitative study explores the uses and gratifications of YouTube, Instagram, and TikTok among 387 undergraduate students at Abubakar Tafawa Balewa University (ATBU). Using a survey design with a 5-point Likert scale questionnaire, data were analyzed with descriptive statistics. Findings indicate YouTube is preferred for educational purposes (M = 4.13, SD = 0.92), followed by Instagram (M = 2.90, SD = 1.10) and TikTok (M = 2.68, SD = 1.15) for entertainment. YouTube has the highest academic benefit (M = 3.59, SD = 1.18) and lowest distraction (M = 2.09, SD = 0.97), while Instagram and TikTok are more distracting (M = 2.64, SD = 1.07; M = 2.63, SD = 1.11). YouTube is widely used for academic tasks (M = 3.74, SD = 1.04) and information access (M = 3.85, SD = 1.03), unlike Instagram (M = 2.71, SD = 1.12) and TikTok (M = 2.62, SD = 1.17). Missed deadlines are minimal across platforms (M = 2.09–2.33). YouTube’s primary motivation is learning (M = 3.95, SD = 1.00), while Instagram and TikTok excel in entertainment (M = 3.56, SD = 1.08; M = 3.66, SD = 1.13) and creativity (M = 3.54, SD = 1.09; M = 3.76, SD = 1.07). the study recommends the integratation YouTube into academic curricula.